2009
DOI: 10.1111/j.1440-1835.2009.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

New species of freshwater Ulva, Ulva limnetica (Ulvales, Ulvophyceae) from the Ryukyu Islands, Japan

Abstract: Ulva limnetica Ichihara et Shimada, sp. nov. (Ulvales, Ulvophyceae) is described from the Ryukyu Islands, Japan, and is characterized by thalli that are: (i) branched, tubular, fragile and wrinkled; (ii) up to 80 cm in height and up to 2 cm in diameter; (iii) light to yellowish green in color; and (iv) having an asexual reproduction by means of quadriflagellate swarmers. Rhizoidal cells bear tubular extensions on the outside of the cell layer in the stipe. Ulva limnetica is distinguished from species with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
0
34
0
5
Order By: Relevance
“…Research so far (Ichihara et al, 2009a(Ichihara et al, , 2009bMareš et al 2011;Ogawa et al 2013) has indicated that either a single Ulva flexuosa species or a complex of separate taxa that are adapted to fresh water occur in inland waters (including those of anthropogenic origin). The objectives of the present study were to: (1) characterize the environmental niches of freshwater Ulva, (2) identify the key habitat parameters that determine the occurrence of Ulva in inland aquatic ecosystems, and (3) clarify limnic Ulva taxa morphologically and genetically in comparison with marine species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research so far (Ichihara et al, 2009a(Ichihara et al, , 2009bMareš et al 2011;Ogawa et al 2013) has indicated that either a single Ulva flexuosa species or a complex of separate taxa that are adapted to fresh water occur in inland waters (including those of anthropogenic origin). The objectives of the present study were to: (1) characterize the environmental niches of freshwater Ulva, (2) identify the key habitat parameters that determine the occurrence of Ulva in inland aquatic ecosystems, and (3) clarify limnic Ulva taxa morphologically and genetically in comparison with marine species.…”
Section: Introductionmentioning
confidence: 99%
“…Three Ulvaceae taxa: Ulvaria obscura var. blyttii (Areschoug) Bliding (1969) (Hayden & Waaland, 2002;Hayden et al, 2003;Ichihara et al, 2009aIchihara et al, , 2009b. Sequences of reference taxa were obtained from the NCBI database, based on the available literature (Supplementary Table 3).…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The group is predominantly marine, but several transitions to freshwater or terrestrial habitats have occurred independently (Shimada et al, 2008;Ichihara et al, 2009;Suutari et al, 2010). The orders Ulvales and Ulotrichales have traditionally been distinguished based on life history features: the Ulvales have a life cycle involving isomorphic alternations of multicellular stages, while in the Ulotrichales the diploid, spore-producing stage is a small, thick-walled unicell that is attached to the substrate by a stalk (Codiolum stage) (O'Kelly et al, 2004b).…”
Section: Ulvophyceaementioning
confidence: 99%
“…The green algal genus Ulva, including species previously placed in the genus Enteromorpha (Hayden et al 2003), is known for its wide distribution in marine, brackish water, and freshwater environments globally (van den Hoek et al 1995, Maggs et al 2007, Shimada et al 2008, Ichihara et al 2009, Mareš et al 2011. A total of 107 species are taxonomically accepted (Guiry and Guiry 2015), of which 29 are currently recognized in Japan (Masakiyo and Shimada 2014).…”
mentioning
confidence: 99%